Optimising Farm Area Allocations Based on Soil Moisture Thresholds: A Comparative Study of Two Dairy Farms with Distinct Soil and Topographic Features - Rumia Basu; Owen Fenton; Gourav Misra; Patrick Tuohy (Agriculture)
On intensive dairy farms, good decision making regarding application of fertilisers and irrigation requires an understanding of soil moisture conditions. Targeted fertiliser application not only contributes to high nutrient use efficiency but reduces the potential for leaching of nutrients and controls emissions from farms. This calls for the development of an improved farm management decision support system focussed on precision agriculture solutions for sustainable agriculture. Knowledge of soil moisture at high resolution at the farm scale can help develop such solutions while at the same time reducing the risk of soil compaction by machinery and/or animals, especially under wet conditions. The objective of this study is to examine and compare two intensive dairy farms, with similar average annual rainfall but contrasting soil (but similar drainage) and topographic characteristics, for their resilience towards extreme conditions (e.g., saturation or drought). Soil moisture thresholds for optimal conditions and corresponding farm area proportions were calculated, identifying areas for targeted farm management. This study addresses the knowledge gap of including high-resolution satellite derived soil moisture as a variable in designing farm management systems targeted towards precision agriculture. Farm 1 was situated in a drumlin belt, whereas Farm 2 had lowland terrain, representing major land cover categories in Ireland. The results showed that Farm 2 was more resilient towards extreme conditions and that the variable topography and soil heterogeneity act as a buffer in regulating moisture regimes on the farm, preventing movement towards the extremes. Across the years, Farm 1 showed less variability in optimal farm area proportions and could be managed better than Farm 2 in terms of overall productivity and resilience towards extreme weather conditions such as droughts, even in a drought year. This study showed that along with variations in soil type, topographic features also dictate water movement and therefore soil moisture regimes on farms.